Energetic and economic analysis of a stand alone photovoltaic system with hydrogen storage. (November 2019) - Marino, C.; Nucara, A.; Panzera, M.F.; Pietrafesa, M.; Varano, V.
Abstract: The study describes a stand-alone photovoltaic system in which the storage is realized using electrolytic hydrogen, converted into electricity in fuel cells. The aim of the research is the optimization of the sizing of the system elements chain (photovoltaic generator, electrolyzer, tank, fuel cell) with respect to the electric load to fulfil. A positive annual balance between hydrogen production and consumption must be guaranteed; furthermore, energy production surplus that cannot be stored or converted into hydrogen due to batteries or tanks capacity limits must be avoided. The energetic analysis and that of hydrogen production and consumption have been carried out on an hourly basis using the HOMER software. The study shows that, being the load active in the evening and the system disconnected from the grid, excess energy cannot be exploited unless large tanks are used, if high gas pressures are to be avoided. Consequently, the system use in public areas or residential buildings, where visual impact generated by tanks is hardly acceptable and safety rules do not allow high gas pressures, is advisable only in grid-connected configurations. Such problems are by far reduced when a marked self consumption is present. Highlights: Hydrogen might represent the energy vector of the future. RES can be used as a primary source for the production of electrolytic hydrogen. Electrolysis of water from RES has only byproducts water and heat. After electrolysis hydrogen is stored and converted into electricity by fuel cells. The study refers to a real stand-alone PV system equipped with hydrogen storage.